2018
DOI: 10.1111/jre.12577
|View full text |Cite
|
Sign up to set email alerts
|

Spheroid culture enhances osteogenic potential of periodontal ligament mesenchymal stem cells

Abstract: Spheroid cultures of hPDLMSCs may be a novel and useful tool in regenerative medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
46
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 45 publications
9
46
2
Order By: Relevance
“…Pennock et al demonstrated that spheroid culture of BM‐MSCs resulted in the induction of autophagy, as well as a shift in the mode of energy production from oxidative phosphorylation to anaerobic; the expression of the stem cell genes Oct4 , Nanog , and Sox2 was enhanced to induce the dedifferentiation of cells. Other previous studies have also reported the enhanced gene expression of Oct4 and Sox2 . We obtained data showing the enhancement of these genes; however, we concluded that this enhancement was derived from genomic DNA contamination, and that spheroid culture of PDLSCs did not increase their expression.…”
Section: Discussionmentioning
confidence: 38%
See 4 more Smart Citations
“…Pennock et al demonstrated that spheroid culture of BM‐MSCs resulted in the induction of autophagy, as well as a shift in the mode of energy production from oxidative phosphorylation to anaerobic; the expression of the stem cell genes Oct4 , Nanog , and Sox2 was enhanced to induce the dedifferentiation of cells. Other previous studies have also reported the enhanced gene expression of Oct4 and Sox2 . We obtained data showing the enhancement of these genes; however, we concluded that this enhancement was derived from genomic DNA contamination, and that spheroid culture of PDLSCs did not increase their expression.…”
Section: Discussionmentioning
confidence: 38%
“…However, we did not find the regeneration of periodontal tissues by transplanting of PDLSC spheroids into periodontal defects in rats, although the sample size was small. There have been several reports that demonstrated the enhancement of tissue regeneration by transplantation of spheroids . Possible explanation of a failure of periodontal regeneration in this study maybe the number of dead cells contained in spheroid.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations